Pengembangan Electronic Load Controller untuk Self-Excited Induction Generator Berbasis Penyearah Tiga Fase Menggunakan Raspberry Pi - Ihsan Nur Hakim; Aan Listanto Amdrian; Adlan Bagus Pradana; Awang Noor Indra Wardana (Jurusan Teknik Elektro Universitas Andalas, 2020)
A self-excited induction generator (SEIG) could provide electricity for isolated areas appropriately. An electronic load controller (ELC) with Raspberry Pi is designed to overcome the voltage and frequency changing of SEIG caused by load changing, while ab le to support distributed system trend with Framework for Distributed Industrial Automation and Control (4DIAC). The ELC design is based on the characteristics of SEIG and Indonesian electricity system standards. The design is then implemented, and the characteristics are identiﬁed. The output of SEIG is regulated at frequency of 50 Hz and terminal voltage of 294 V. A voltage sensor is designed with a transformer, ﬁlters, rectiﬁer, and ADC. The actuator consisted of a three-phase rectiﬁer, dump load, optocoupler driver, and IGBT. A PI-controller based on Python is applied in Raspberry Pi Zero with experimentally tuned Kp and Ki values both of 5.0. The output changing of SEIG caused by load changing could be regulated within the Indonesian electricity frequency standard in its steady state. The maximum voltage deviation from the nominal value is -12.24%, while the maximum frequency deviation is +3.2%, and the longest settling time is 832 ms.Keywords : induction generator, electronic load controller and Raspberry Pi.